2013
DOI: 10.1002/adhm.201200400
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Electrostatics and Temperature on Morphological Transitions of Hydrogel Nanostructures Self‐Assembled by Peptide Amphiphiles Via Molecular Dynamics Simulations

Abstract: Smart biomaterials that are self-assembled from peptide amphiphiles (PA) are known to undergo morphological transitions in response to specific physiological stimuli. The design of such customizable hydrogels is of significant interest due to their potential applications in tissue engineering, biomedical imaging, and drug delivery. Using a novel coarse-grained peptide/polymer model, which has been validated by comparison of equilibrium conformations from atomistic simulations, large-scale molecular dynamics si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 57 publications
5
79
0
Order By: Relevance
“…In this study, the value for R, which is interpreted as the degree of hydrophobicity between nonpolar groups and is governed by the particular solvent choice, is kept constant at R = 1/3 based on prior work in our group that has established this reference condition for the formation of prototypical cylindrical nanofibers. 42,44,45 Comparison of our structures 42 showed a high degree of similarity with those observed in experimental structures. 2,12 Moreover, the simulations that were conducted by the Schatz group using atomistic and coarsegrained models 52−54 with explicit solvents produce similar structures as those observed by our simulations.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…In this study, the value for R, which is interpreted as the degree of hydrophobicity between nonpolar groups and is governed by the particular solvent choice, is kept constant at R = 1/3 based on prior work in our group that has established this reference condition for the formation of prototypical cylindrical nanofibers. 42,44,45 Comparison of our structures 42 showed a high degree of similarity with those observed in experimental structures. 2,12 Moreover, the simulations that were conducted by the Schatz group using atomistic and coarsegrained models 52−54 with explicit solvents produce similar structures as those observed by our simulations.…”
Section: Methodssupporting
confidence: 74%
“…42 We performed replica-exchange simulations using both atomistic CHARMM 27 force field 59−61 and ePRIME models to examine the effect of temperature on the folding process of a single PA1 molecule. Equilibrium results showed that both coarse-grained and all-atom models produce similar conformations over a wide range of temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the WT4 model, which condenses 11 water molecules in four beads, was meant to work in conjunction with the SIRAH force-field [142]. In the same way, the regular and polarized water models by The model developed by Nguyen and coworkers was thought to combine with ePRIME [152], and be delivered as BioModi [149], a unified CG force-field for DNA, proteins and general polymers. The DNA model from Scheraga's group [128] was derived with the same philosophy used to derive the UNRES [153] force-field for proteins, and is expected to be compatible.…”
Section: Coarse-grain Studiesmentioning
confidence: 99%